2020
DOI: 10.1101/2020.07.22.215897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phosphoproteomic Identification of Vasopressin-Regulated Protein Kinases in Collecting Duct Cells

Abstract: Background and PurposeThe peptide hormone vasopressin regulates water transport in the renal collecting duct largely via the V2 receptor, which triggers a cAMP-mediated activation of a protein kinase A (PKA)-dependent signaling network. The protein kinases downstream from PKA have not been fully identified or mapped to regulated phosphoproteins.Experimental ApproachWe carried out systems-level analysis of large-scale phosphoproteomic data quantifying vasopressin-induced changes in phosphorylation in aquaporin-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…It has been observed that platelet activations, endothelial dysfunction and thrombosis in SARS-CoV-2 are due to activation of mitogen-activated protein kinase (MAPK) leading to pulmonary micro-vascular thrombosis and progression of ALI/ARDS [58] . Notably, AVP triggers MAPK-induced endothelial dysfunction with direct effect for release of clotting factors [59] , [60] . Remarkably, administration of AVP reduces development of ALI [61] however, Barcroft et al, illustrated in a case-report study that intramyometrial infiltration of AVP during laparoscopic myomyectomy leads to acute pulmonary edema and coronary vasospasm [62] .…”
Section: Arginine Vasopressin and Covid-19mentioning
confidence: 99%
“…It has been observed that platelet activations, endothelial dysfunction and thrombosis in SARS-CoV-2 are due to activation of mitogen-activated protein kinase (MAPK) leading to pulmonary micro-vascular thrombosis and progression of ALI/ARDS [58] . Notably, AVP triggers MAPK-induced endothelial dysfunction with direct effect for release of clotting factors [59] , [60] . Remarkably, administration of AVP reduces development of ALI [61] however, Barcroft et al, illustrated in a case-report study that intramyometrial infiltration of AVP during laparoscopic myomyectomy leads to acute pulmonary edema and coronary vasospasm [62] .…”
Section: Arginine Vasopressin and Covid-19mentioning
confidence: 99%
“…The downstream targets of PKA that mediate PKA-induced AQP2-S261 dephosphorylation and AQP2-S269 phosphorylation remain unknown. Quantitative phosphoproteome analysis of mpkCCD cell lines in the presence or absence of vasopressin revealed that six protein kinases (Sik2, Cdk18, Camkk2, Prkd2, Mapk3, and Mylk) were involved in the vasopressin/cAMP/PKA signaling pathway [ 18 ]. In addition to kinases, phosphatases in the vasopressin signaling pathway contribute to AQP2 phosphorylation [ 19 ].…”
Section: Importance Of Pka In Aqp2 Regulationmentioning
confidence: 99%